Behavioural analysis of interactions between pedestrians and vehicles in street designs with elements of shared space. (April 2015) - Kaparias, I.; Bell, M.G.H.; Biagioli, T.; Bellezza, L.; Mount, B.
Highlights: Development of a new method for the behavioural analysis of vehicle–pedestrian interactions. Application to an urban road site before and after redevelopment to shared space. Greater interaction between pedestrians and vehicles post-redevelopment. Driver behaviour relatively unchanged. Increased pedestrian confidence in their interaction with vehicles. Abstract: This paper describes the development and implementation of qualitative behavioural criteria in order to analyse the conduct of pedestrians and vehicles when they are required to interact with each other, with particular interest to street designs with elements of shared space. The new behavioural analysis technique is developed by identifying the fundamental principles that underpin existing traffic analyses, such as traffic conflicts techniques, and adapting those to a qualitative framework that describes the mindset and rationale of road users. The technique is then applied to a case study in London, using video data from periods before and after the redevelopment of the Exhibition Road site from a conventional dual carriageway to a modern design with some elements of shared space. With the main goals being to assess the pedestrians' confidence and the vehicles' tolerance/patience when forced to interact with each other, behavioural trends are related to instantaneous characteristics of the vehicle flow (vehicle approach speed and traffic density). The data produced are used to develop and validate qualitative behavioural relationships for pedestrian–vehicle interactions, as well as location-specific conclusions for the Exhibition Road site.